Analysis of early efficacy and immune reconstitution after autologous hematopoietic stem cell transplantation in multiple myeloma - Kaili Chen; Huixin Liang; Zezhong Yu; Guangyao Guo; Huijian Zheng; Yun Huang; Liping Liu; Jie Lin; Jinlan Long; Renyao Pan; Xi Chen; Changgui Wang; et al. (Scientific Reports)
Abstract This retrospective study aimed to stress the advantages of autologous hematopoietic stem cell transplantation (auto-HSCT) in treating primary MM. Ninety-four MM patients who underwent initial parallel sequential auto-HSCT were selected. Data on efficacy (efficacy evaluation, renal function and hemoglobin recovery), immune reconstitution (B-cell subsets, immunoglobulin levels, T-cell subsets, NK cells, neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR)) and hematopoietic reconstitution times were collected and analyzed. Whether in all selected patients or in groups R-ISS II-III, there was a notable increase in the proportion of patients achieving in a very good partial response (VGPR) or better (P < 0.001, P = 0.02) and a complete response (CR) or better (P = 0.007, P = 0.014) after transplantation compared to the pre-transplant status. Post-Transplant Immune Reconstitution Analysis (Baseline vs. Pre-Transplant and Pre-Transplant vs. Post-Transplant): The level of CD19 + B cells, CD20 + B cells, CD22 + B cells, CD3 + T cells, IgG and LMR showed the same change trend, that is, it decreased before transplantation (P < 0.001, P < 0.001, P < 0.001, P < 0.001, P<0.007, P < 0.001) and then increased significantly after transplantation(P < 0.001, P < 0.001, P < 0.001, P < 0.001, P < 0.001, P < 0.001). CD3 + CD4 + T cells from 545.97 (342.11,708.60)/µL to 342.93 (168.38, 475.52)/µL (P < 0.001) and then to 251.48 (188.52, 406.98)/µL (P = 0.348); CD3 + CD8 + T cells from 391.36 (242.19, 563.37)/µL to 337.23 (192.54, 505.96)/µL (P = 0.065) and then to 797.96 (514.49, 1198.03)/µL (P < 0.001), so the CD3 + CD4+/CD3 + CD8 + T cell ratio still remained inverted post-transplant. NK cells changed from 309.86 (206.33, 460.96)/µL to 258.31 (160.75, 436.68)/ µL (P = 0.229) and then to 151.08 (108.17, 240.84)/µL (P = 0.007). Auto-HSCT can promote prolonged remission in patients with MM and also overcome some high-risk factors to achieve superior efficacy in group R-ISS II-III. Patients were immunodeficient before transplantation and auto-HSCT facilitated immune reconstitution.